The mentalization-based therapy adherence and quality scale (MBT-AQS): Reliability in a clinical setting. Issue 2 (3rd April 2019) - Simonsen, Sebastian; Juul, Sophie; Kongerslev, Mickey; Bo, Sune; Folmo, Espen; Karterud, Sigmund
Abstract: The Mentalization - Based Treatment Adherence and Quality Scale (MBT-AQS) is a 17-item measure of treatment adherence and quality of individual mentalization-based therapy (MBT). Until now, reliability research on the scale has primarily been conducted by highly experienced raters from the Norwegian MBT Quality Lab who were part of its development. Hence, it can be questioned whether only experts in research settings can achieve satisfying levels of reliability on the scale. In this study, we investigated whether a satisfying level of reliability on the MBT-AQS could be obtained by experienced MBT therapists in a clinical setting following a brief one-day training course. The overall reliabilities for six raters were good for adherence (.67) and for quality (.62). Thus, the MBT-AQS was found to be an appropriate MBT adherence rating instrument with clinical and educational utility outside of the Norwegian MBT Quality Lab. However, ambiguity of some constructs, low frequency of certain item ratings and low levels of MBT quality challenge reliability. This is discussed in the context of utilizing the scale for clinical and supervising purposes